Penyelesaian Sengketa Arbitrase dan Kepailitan Syariah Di Pengadilan Agama - Siti Romlah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Even though it has been more than 15 years that the authority to resolve Islamic economic disputes has become the absolute authority of the religious courts, the actualization and practice of this authority is still being debated both among practitioners and academics. This study aims to examine the capacity of the religious courts in resolving sharia economic disputes which are analyzed based on the effectiveness theory of Lawrence M. Friedmann. Especially with regard to the authority to resolve sharia economic disputes, especially in the field of arbitration and bankruptcy dispute resolution. This research uses normative juridical research methods. The results of the study stated that tracing legal elements regarding the resolution of sharia economic disputes related to arbitration and bankruptcy in the religious courts can be seen that the authority of the religious courts in resolving sharia economic disputes related to arbitration has been effective in contrast to the resolution of sharia economic disputes related to bankruptcy which looks less effective. This is due to the lack of legal instruments (substance) governing bankruptcy settlement with regard to sharia economics in the religious courts as well as people's preferences that are still oriented towards commercial courts.Keywords: Sharia Economic Dispute Resolution; Sharia Arbitration; Bankruptcy and PKPU; Religious Court AbstrakMeski sudah lebih dari 15 tahun kewenangan penyelesaian sengketa ekonomi syariah menjadi kewenangan absolut pengadilan agama, namun aktualisasi dan praktik dari kewenangan tersebut masih menjadi perdebatan baik di kalangan praktisi dan akademisi. Penelitian ini bertujuan untuk meneliti kapasitas pengadilan agama dalam menyelesaikan sengketa ekonomi syariah yang dianalisis berdasarkan teori efektivitas Lawrence M. Friedmann. Terlebih terkait kewenangan penyelesaian sengketa ekonomi syariah khususnya di bidang penyelesaian sengketa arbitrase dan pailit. Penelitian ini menggunakan metode penelitian yuridis normatif. Hasil penelitian menyatakan bahwa penelusuran unsur-unsur hukum mengenai penyelesaian sengketa ekonomi syariah terkait arbitrase dan kepailitan di peradilan agama dapat terlihat bahwa kewenangan peradilan agama dalam penyelesaian sengketa ekonomi syariah terkait arbitrase telah berjalan efektif berbeda dengan penyelesaian sengketa ekonomi syariah terkait kepailitan yang terlihat kurang efektif. Hal tersebut disebabkan kurangnya instrumen hukum (substance) yang mengatur mengenai penyelesaian kepailitan berkenaan dengan ekonomi syariah di peradilan agama serta preferensi masyarakat yang masih berkiblat kepada pengadilan niaga.Kata Kunci: Sengketa Ekonomi Syariah; Arbitrase Syariah; Kepailitan dan PKPU; PA